MEN’S 100-METER FREESTYLE: A TEMPORAL AND BIOMECHANICAL ANALYSIS - RĂSĂDEAN, Marcel; BĂLAȘ, Bianca; PÎRJOL, Dan Ionuț (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Men’s 100-meter freestyle event represents a benchmark discipline in competitive swimming, marked by biomechanical complexity, intense physiological demands, and distinctive strategic dynamics. With a longstanding tradition in international competitions, this event requires an optimal combination of speed, power, technique, and recovery capacity. The main objective of this research was to analyze the biomechanical and temporal parameters of the world’s top swimmers in the 100-meter freestyle, in order to identify execution patterns that can contribute to optimizing performance. The study involved a comparative analysis of twelve elite athletes, examining indicators such as split times across the two 50-meter segments, number of stroke cycles, and stroke amplitude. Data were collected from official international competition sources and interpreted through the lens of applied biomechanics. Findings revealed that the highest-performing athletes exhibit minimal temporal and biomechanical amplitude differences between race segments. Pan Zhanle set a new world record (46.40 s), characterized by a well-balanced start and consistent speed maintenance. The analysis of stroke count highlighted the swimmers’ ability to sustain technical stability despite increased metabolic load. The research confirms the hypothesis that top performance in the 100-meter freestyle is decisively influenced by biomechanical balance and strategic effort distribution. Effective strategies are associated with minimal variation in stroke frequency and split times—critical factors in achieving elite-level results. This study provides a relevant analytical framework for coaches and high-performance swimmers, contributing to the development of evidence-based training methodologies in competitive swimming.